Território e participação social: análise da construção do programa Territórios da Cidadania do Pontal do Paranapanema - Arruda, Raquel Carvalho de [UNESP] (2015)
The territorial approach created by international institutions just as the Inter-American Institute for Cooperation on Agriculture and the World Bank presents a proposal of development based on a territory of consensus permeated by processes of participation. Contrarily, the idea of development based on conflict and participation practices brings intrinsically the search for autonomy. In this perspective, we analyse the adoption of the territorial approach in Brazilian social politics what has culminated in the formulation of the programme Territories of Citizenship. By analysing the dynamics of the Territory of Pontal do Paranapanema, we seek to understand its implementation and execution through investigating its origins, aims, institutional relations and main results obtained until the year 2012. To do so, the research included the analysis of the process of territorial formation of Pontal do Paranapanema, which is an expression of dispute for different models of development evolving agents like State, social movements of struggle for land and agribusiness. Moreover, the research comprised the participation in different activities of both the territorial collegiate and the monitoring and information cell, just as the making of interviews with different agents that participate of the process directly. All that together with the readings made possible an interpretation about the construction of this concrete experience. Tow analytical axes were considered as historical processes: social participation and production of territory. General challenges of development, particularities and singularities of a specific region of São Paulo state were articulated in those axes. Therefore, it was possible to identify advances, challenges and limitations of this current experience